China : Improving Rural Public Finance for the Harmonious Society - World Bank (Washington, DC, 2012)
This report aims to assist the government in improving implementation of the New Socialist Countryside (NSC) program, especially in raising the effectiveness of public expenditures, and the harmonization of public finance. While this report pays particular attention to rural aspects of public finance, it addresses this topic within the overall framework of intergovernmental finance that impacts both rural and urban areas. Similarly, the discussions and recommendations in this report are intended to move the system towards one that is harmonized and does not differentiate between 'rural' and 'urban' areas. The structure of this report is as follows: Chapter 2 analyzes the considerable number of reform efforts that have been introduced to the rural public finance system. It looks at the RFR in depth, as well as other associated and related reforms and evaluates the overall outcome of these reforms. Chapter 3 provides an overview of China's intergovernmental system as the framework for rural public finance. It includes an analysis of the expenditure and revenue assignments and their development, and the impact on rural public finance. The transfer system, an integral part of the intergovernmental fiscal system, is treated separately in Chapter 4 because of its overwhelming importance for rural public finance. The chapter analyzes how far the transfer system goes in addressing the fiscal imbalances and providing the necessary public funds for rural areas. It also assesses the role of earmarked transfers. Chapter 5 then looks at the public finance situation at the grassroots level, i.e., the financing of villages, townships, and counties, including how recent developments have impacted their situation and what remaining issues exist at these levels. Finally, Chapter 6 summarizes the findings of this study, proposes a strategy for policy reforms, and suggests ideas for its implementation.